Design of an AC Driving Waveform Based on Characteristics of Electrowetting Stability for Electrowetting Displays - Liu, Linwei; Wu, Zhuoyu; Wang, Li; Zhang, Taiyuan; Li, Wei; Lai, Shufa; Bai, Pengfei (Frontiers in Physics, 2020)
In traditional electrowetting display (EWD) drivers, direct current (DC) voltage and pulse width modulation (PWM) are often used, which easily caused an electrowetting charge trapping phenomenon in a hydrophobic insulating layer. Therefore, the driving voltage must be increased for driving EWDs, and oil backflow cannot be solved. Aqueous solutions are often used as polar liquids for EWDs, and the reverse voltage of alternating current (AC) driving can cause chemical reactions between water and ITO. So, a driving waveform was proposed, which included a DC waveform and an AC waveform, to separately drive EWDs for oil rupture and open state. Firstly, a DC waveform was used when the oil was broken, and the response time was reduced by designing the DC voltage and duration. Secondly, an AC waveform was used when the oil required to be stable. Oil backflow could be suppressed by the AC waveform. The main parameters of AC waveform include reverse voltage, frequency and duty cycle. The reverse voltage of EWDs could be obtained by voltammetry. The frequency could be obtained by analyzing the rising and falling edges of the capacitance voltage (CV) curve. The experimental results showed that the proposed waveform can effectively suppress oil backflow and shorten the response time. The response time was about 86% lower than the conventional driving waveforms, and oil backflow was about 72% slower than the DC driving waveform.